Halotolerant endophytes promote grapevine regrowth after salt-induced defoliation - Salvadora Navarro-Torre; Sara Ferrario; Ana D. Caperta; Gonçalo Victorino; Marion Bailly; Vicelina Sousa; Wanda Viegas; Amaia Nogales (Journal of Plant Interactions, 2023)
ABSTRACTSalinity is an important problem for agriculture in the Mediterranean area, and thus, it is essential to develop mitigation strategies to reduce its impact. The main objective of this study was to test the effectiveness of halotolerant plant growth-promoting bacteria (H-PGPB) in improving grapevine salt stress tolerance. Grapevines grafted onto a salt-sensitive rootstock were inoculated with a consortium of H-PGPB. The substrate of half of the plants of each treatment was salinized up to 2 dS m−1. Plants grew for six days under these conditions, and afterward, NaCl was removed to assess plant recovery through growth, physiology, and canopy temperature measurements. Inoculation with H-PGPB had a positive effect on plant physiology, but after salt treatment, grapevines stopped their photosynthetic metabolism, leading to severe defoliation. Remarkably, after salt stress removal, inoculated plants re-sprouted faster, demonstrating that H-PGPB inoculation could be a good practice to increase vineyard resilience to salt stress.